The Public Transport Users Mode Choice and Its Determinants in Addis Ababa City - Tazzie, Yibeltal Dubale (Journal of Urban Development Studies, 2023)
This study investigates the public transport mode choice and its determinants in Addis Ababa, focusing on two major public transport corridors: East-West (Ayat - Torhailoch) and North-South (Piassa - Kality). For this study data were collected from 665 public transport users through questionnaires and 15 key informants through interviews, as well as desk reviews. The data were analyzed using descriptive and inferential statistics with the help of SPSS version 26 and Microsoft Excel. The study reveals poor public transport service in the study area, with 80.3% of the respondents dissatisfied with availability, accessibility, affordability, safety, and security of the public transport systems. Many respondents traveled 0.5-1 km to reach stations and experienced long waiting times, exceeding average African passenger waiting times (30 minutes).The result also shows that demographic factors such as such as age, occupation, education level, and monthly income, as well as waiting time, cost, comfort, reliability and perception significantly affects the public transport mode choice. From the multinomial logistic regression, the Nagelkerke Pseudo R-squared value is 0.652, suggesting that the model accounts for around 65.2% of the variation of dependent variable explained by the independent variables.These findings provide valuable insights for policymakers to make informed decisions and improve public transport services that can satisfy the public transport users mode preferences behavoiurs. The study emphasizes the need for policy interventions to enhance the quality, accessibility, and affordability of public transport services.